2020
DOI: 10.4317/medoral.23289
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis and evaluation of the journal Medicina Oral Patología Oral y Cirugía Bucal (2008-2018)

Abstract: Background: In 2008 the journal Medicina Oral Patología Oral y Cirugía Bucal was included in Journal Citation Reports. To appraise its evolution and current status, this study carried out a bibliometric analysis and evaluation of the journal for the period 2008-2018. Material and Methods: From the Web of Science, Journal Citation Reports we obtained the indicators Journal Impact Factor (JIF), 5-year JIF, JIF without self-cites, Eigenfactor score and Article Influence score (2010-2017); and from the Core Collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Since this is the first study that evaluated Bibliographic information of publications about oral health and cerebral palsy, no other study was found to compare to the 31 Case-report found in this study. Liu et al (2020) evaluated traumatic dental injuries in a bibliometric analysis over two decades (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018), and found that most articles were case reports. However, it should be noted that the conclusions of case-reports could not be applied directly in clinical practice (Hurd 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this is the first study that evaluated Bibliographic information of publications about oral health and cerebral palsy, no other study was found to compare to the 31 Case-report found in this study. Liu et al (2020) evaluated traumatic dental injuries in a bibliometric analysis over two decades (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018), and found that most articles were case reports. However, it should be noted that the conclusions of case-reports could not be applied directly in clinical practice (Hurd 2014).…”
Section: Discussionmentioning
confidence: 99%
“…After ten years of scientific production published in Acta Stomatologica Croatica, regarding the affiliation of the corresponding author, there was a higher frequency of publications of foreign origin (53.0%), Brazil had a greater contribution in these publications (25.9%) (de Araújo et al 2020). In the journal Medicina Oral Patología Oral y Cirugía Bucal (2008Bucal ( -2018 authors from 70 countries published 1,518 documents; Spain represents 48.68%, followed by Brazil (15.55%) and Turkey (7.38%) (Valderrama et al, 2020). It is possible to notice that Brazil stands out in the publications of dentistry nationally and internationally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When studying temporal evolution, there is an increasing trend in scientific production as the years go by. This tendency toward exponential growth of publications can be observed in bibliometric studies on scientific production in areas such as Implantology [5] , Periodontics [8] , Dental Pathology and Therapeutics [15], and Oral Medicine [16] . This trend has also been observed in reviews [2].…”
Section: Discussionmentioning
confidence: 99%